Error Analysis of the Use of Question Words in English Sentences - Nurjanah Nurjanah; Doni Anggoro; Nina Dwiastuty (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2018)
The research aims to analyze the error in using questions word on second grade students of MTs. Hidayatussalafiyah. Question is one of important aspect that students need to master not only in writing but also speaking. There are several types of questions that students need to learn. The types of questions that discuss in this research are “Yes/No-Questions” and “Wh-Questions”. The data are collected through observation, discussion, books and also documentation. By the data, the research finds the most error the students made in each category. The research findings also prove the students need more explanation in forming questions especially in writing. Based on the result, the student faced more difficult in forming “Yes/No-Questions” than in “Wh-Questions” category. They made mistake for 298 or 65.07% in “Yes/No-Questions and 160 or 34.93% in “Wh-Questions” from the total mistakes. The most difficult question for them in “Yes/No-Questions” is to form “are you studying your grammar book?” or using “be (is/am/are) in present progressive tense”. The total number of mistakes for this questions are 26 or 8.4%. And, for the “Wh-Questions”, they made more mistake to form “what time did you eat lunch?” or using “what time” to ask about the time. Key words: error, analysis, question words